063 Anti-MOG and anti AQP4 antibodies in pediatric acquired memyelinating syndromes (ADS): an Indian cohort. Issue 6 (27th May 2022) - Sankhyan, Naveen; Rawat, Amit; Vyas, Sameer; Sahu, Jitendra; Priyanka, Chandana; Saini, Lokesh; Saini, Arushi; Suthar, Renu; Sukhija, Jaspreet; Murlidharan, Jayashree
Abstract : Aim: To determine positivity to myelin oligodendrocyte glycoprotein (MOG-Ab) and aquaporin-4 antibod- ies (AQP4-Ab) in children with Pediatric Acquired Demyelinating Syndromes (ADS). Method: Prospectively, in one centre, between May 2018 and Sep 2019, children (6 mo- 15 yrs) with suspected ADS were enrolled and tested for MOG-Ab and AQP4-Ab. Children with a proven non-immune mediated neurological disease were enrolled as controls. Results: Seventy-nine children with suspected ADS were screened and 72 enrolled. There were 29 with acute disseminated encephalomyelitis (ADEM), 22 with optic neuritis and 19 with myelitis. Fourteen (19.4%, 95% CI 11–30.5) tested positive for one antibody [12 ( 17%, 95% CI 9–27) tested positive for MOG-Ab and two ( 3%, 95% CI 0.3–10) for AQP4-Ab]. None of the 62 controls tested positive for any antibody. Among those with first event, 7/58 (9%, 95% CI 3–19%) were MOG-Ab positive and two AQP4-Ab positive, whereas, 7/14 (50%, 23–77%) with recurrent events were MOG-Ab positive. All four with multiphasic ADEM were MOG Ab (4/4) positive. One of the 19 with myelitis was MOG-Ab positive. Conclusions: Detected in one in five children, MOG-Ab are the most common antibodies detected in Pediatric ADS, especially in relapsing disease. AQP4-Ab are rare in children with ADS. drnsankhyan@yahoo.co.in